Molecular characterization and antimicrobial susceptibility for 62 isolates of Bordetella pertussis from children - He, Baohua; Jia, Zhaoyi; Zheng, Fei; Zhang, Wenchao; Duan, Suxia; Wang, Leyu; Zhang, Haixia; Zhang, Hongbin; Wang, Ruoxuan; Gao, Yuan; Sun, Yinqi (Frontiers in Microbiology, 2024)
BackgroundPertussis is a highly contagious respiratory disease caused by Bordetella pertussis (BP). Despite global control of pertussis cases through the Expanded Programme on Immunization (EPI), there has been a significant increase in the incidence of pertussis in recent years, characterized by a “resurgence” in developed countries with high immunization rates as well as a comparable reemergence in certain areas of China. We aim to explore the genotypes and antimicrobial susceptibility of circulating BP from children in Hebei.Study designChildren diagnosed with BP infection from 2019 to 2020 in Hebei, China were enrolled. We performed antimicrobial susceptibility testing (AST), whole-genome sequencing (WGS) analysis, single nucleotide polymorphism (SNP) detection, mltilocus sequence typing (MLST), multilocus antigen sequence typing (MAST), multilevel genome typing (MGT). A total of 313 international BP genomes were selected for comparison to examine the genomic diversity and evolutionary traits of Chinese strains within a global framework.ResultsSixty-two individuals were identified with BP infection via culture, yielding a positive rate of 15.62% (62/397) for BP. Two phylogenetic groups were identified, each carrying a dominating genotype. The two vaccine strains, CS and Tohama I, exhibited a distant relationship to these two groups. This study identified 56 erythromycin-resistant isolates, 55 azithromycin-resistant isolates, 58 sulfamethoxazole-sensitive isolates, and 53 cefotaxime-sensitive isolates. All BP isolates were sensitive to levofloxacin, amoxicillin, ceftriaxone, and meropenem. Meanwhile, all erythromycin-resistant strains, which belonged to lineage I and MGT2 sequence type 7 (ST7), shared the ptxP1 gene and contained the 23S rRNA A2047G mutation. The major MAST was prn1/ptxP1/ptxA1/fim3-1/fim2-1 (75.81%). All 62 BP strains were divided into 1, 2, 3, 14, and 52 types at the MGT1, MGT2, MGT3, MGT4, and MGT5 levels, respectively.ConclusionThis work showed that there may be a link between antimicrobial resistance and alterations in specific molecular types, and the isolates showed a clear change when compared with the vaccine strain and that selection pressure from both antibiotics and immunization may be responsible for driving Chinese BP evolution, and necessitate a reevaluation of the immunization strategy and the development of novel vaccines in China to halt the resurgence and medication resistance of pertussis.